ASTEROID SEARCH RESULTS FOR DIGITIZED ASTROPLATES OF 1.2m TELESCOPE IN BALDONE - Eglitis, I.; Yizhakevych, O.; Shatokhina, S.; Protsyuk, Yu.; Andruk, V. (Одеські астрономічні публікації, 2019)
The work on the mass search for asteroids on astroplate images and the determination of their coordi- nates was begun in 2016. The basis for current search was the processing results of digitized photographic plates and films obtained at the observatory in Baldone in 1967-1993. Observations with a single exposure in different spectral bands were carried out using the 1.2m Schmidt telescope in Baldone. We used all observations in the U Johnson's spec- tral band (on plates) and significant part of them in V band (on films). Photometric band U was realized by combining emulsion ORWO Zu1 (Zu2 or Zu21 or Kodak 103aO or IIaO) with UG1 filter. For films with A600 emulsion and filter ZS17 a photometric band V was implemented. Based on the results of digital processing about 300 U- plates and more than 1460 V-films, a preliminary catalog of 1700 asteroid positions was compiled. Among the ob- jects in this catalog are asteroids of particular interest. These include the distant objects (136108) Haumea and (136472) Makemake and some Main belt asteroids, the positions of which were fixed on the plates many years before their own discoveries. All observed positions of asteroids were compared with ephemeris DE431. An analysis of the convergence of the observed positions with their theoretical data for different spectral bands showed that the observations on V-films are better consistent with theory. However, the internal accuracy of determining coordi- nates from U-plates, on the contrary, is higher than from V-films. This discrepancy is especially noticeable for right ascension, when the root-mean-square errors on V-films can reach values exceeding 1.8 arc seconds. These signifi- cant errors are a consequence of the curvature unevenness of the film surface during scanning